Faktor-faktor yang mempengaruhi Opini Audit Going Concern: Kualitas Audit, Manajemen Laba, dan Mekanisme Corporate Governance - Shella Juniet Dubelta; Cris Kuntadi; Supaijo Supaijo (Jurnal Pajak dan Analisis Ekonomi Syariah, 2024)
The purpose of this research aims to determine the influence of Audit Quality, Profit Management, and Corporate Governance Mechanisms on Going Concern Audit Opinions. This article reviews the factors that influence Going Concern Audit Opinions, namely Audit Quality, Earnings Management, and Corporate Governance Mechanisms, a study of tax accounting literature. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this literature review article are: 1) Audit Quality influences Going Concern Audit Opinion; 2) Earnings Management influences Going Concern Audit Opinion; and 3) Corporate Governance mechanisms influence the Going Concern Audit Opinion.